Multifunctional Janus-Structured Polytetrafluoroethylene-Carbon Nanotube-Fe3O4/MXene Membranes for Enhanced EMI Shielding and Thermal Management - Shao, Runze; Wang, Guilong; Chai, Jialong; Lin, Jun; Zhao, Guoqun; Zeng, Zhihui; Wang, Guizhen (Nano-Micro Letters, 2025)
Herein, a novel Janus-structured multifunctional membrane with integrated electromagnetic interference (EMI) shielding and personalized thermal management is fabricated using shear-induced in situ fibrillation and vacuum-assisted filtration. Interestingly, within the polytetrafluoroethylene (PTFE)-carbon nanotube (CNT)-Fe3O4 layer (FCFe), CNT nanofibers interweave with PTFE fibers to form a stable “silk-like” structure that effectively captures Fe3O4 particles. By incorporating a highly conductive MXene layer, the FCFe/MXene (FCFe/M) membrane exhibits excellent electrical/thermal conductivity, mechanical properties, and flame retardancy. Impressively, benefiting from the rational regulation of component proportions and the design of a Janus structure, the FCFe/M membrane with a thickness of only 84.9 µm delivers outstanding EMI shielding effectiveness of 44.56 dB in the X-band, with a normalized specific SE reaching 10,421.3 dB cm2 g−1, which is attributed to the “absorption-reflection-reabsorption” mechanism. Furthermore, the membrane demonstrates low-voltage-driven Joule heating and fast-response photothermal performance. Under the stimulation of a 3 V voltage and an optical power density of 320 mW cm−2, the surface temperatures of the FCFe/M membranes can reach up to 140.4 and 145.7 °C, respectively. In brief, the FCFe/M membrane with anti-electromagnetic radiation and temperature regulation is an attractive candidate for the next generation of wearable electronics, EMI compatibility, visual heating, thermotherapy, and military and aerospace applications. Highlights: 1 The Janus-type multifunctional ultra-flexible polytetrafluoroethylene-carbon nanotube-Fe3O4/MXene (FCFe/M) membranes were fabricated via a shear-induced in situ fibrillation technique followed by vacuum-assisted filtration. 2 Thanks to the strategic distribution of the MXene conductive reflection layer and the silk-like FCFe electromagnetic wave’s absorption layer, the membranes achieve robust electromagnetic interference shielding and effective antireflection through the absorption-reflection-reabsorption mechanism. 3 The membranes exhibit exceptional thermal management performance, including efficient heat dissipation and electrothermal/photothermal conversion capabilities, further enhancing their promising potential for applications in flexible wearable technologies.